Migration and outbreaks of vaccine-preventable disease in Europe: a systematic review. Issue 12 (December 2021) - Deal, Anna; Halliday, Rae; Crawshaw, Alison F; Hayward, Sally E; Burnard, Amelia; Rustage, Kieran; Carter, Jessica; Mehrotra, Anushka; Knights, Felicity; Campos-Matos, Ines; Majeed, Azeem; Friedland, Jon S; et al.
Summary: Migrant populations are one of several underimmunised groups in the EU or European Economic Area (EU/EEA), yet little is known about their involvement in outbreaks of vaccine-preventable diseases. This information is vital to develop targeted strategies to improve the health of diverse migrant communities. We did a systematic review (PROSPERO CRD42019157473; Jan 1, 2000, to May 22, 2020) adhering to PRISMA guidelines, to identify studies on vaccine-preventable disease outbreaks (measles, mumps, rubella, diphtheria, pertussis, polio, hepatitis A, varicella, Neisseria meningitidis, and Haemophilus influenzae ) involving migrants residing in the EU/EEA and Switzerland. We identified 45 studies, reporting on 47 distinct vaccine-preventable disease outbreaks across 13 countries. Most reported outbreaks involving migrants were of measles (n=24; 6496 cases), followed by varicella (n=11; 505 cases), hepatitis A (n=7; 1356 cases), rubella (n=3; 487 cases), and mumps (n=2; 293 cases). 19 (40%) outbreaks, predominantly varicella and measles, were reported in temporary refugee camps or shelters. Of 11 varicella outbreaks, nine (82%) were associated with adult migrants. Half of measles outbreaks (n=11) were associated with migrants from eastern European countries. In conclusion, migrants are involved in vaccine-preventable disease outbreaks in Europe, with adult and child refugees residing in shelters or temporary camps at particular risk, alongside specific nationality groups. Vulnerability varies by disease, setting, and demographics, highlighting the importance of tailoring catch-up vaccination interventions to specific groups in order to meet regional and global vaccination targets as recommended by the new Immunisation Agenda 2030 framework for action. A better understanding of vaccine access and intent in migrant groups and a greater focus on co-designing interventions is urgently needed, with direct implications for COVID-19 vaccine delivery.